Investigating teaching and learning of Grade 9 Algebra through excel spreadsheets : a mixed-methods case study for Lesotho - Ntsohi, Mamosa M. E. (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)-- Stellenbosch University, 2013.